The earnings of immigrants in Ireland: results from the 2005 EU survey of income and living conditions - Alan Barrett; Yvonne McCarthy (Institute for the Study of Labor (IZA), 2007)
This paper has three objectives. First, a review of the developing body of work on the economics of immigration in Ireland is provided. Second, the analysis undertaken by Barrett and McCarthy (forthcoming) of earnings of immigrants in Ireland is updated. Third, the earnings of immigrant women are assessed to see if they experience a double disadvantage. Among other findings, the review of the emerging literature points to immigrants faring less well in the Irish labour market relative to native employees. As regards the analysis conducted in this paper, we find that immigrants were earning 15 percent less than comparable natives employees in 2005. For immigrants from non-English speaking countries, the wage disadvantage was 20 percent. The corresponding figure for immigrants from the EU's New Member States was 31 percent. A double disadvantage is found for immigrant women, with the earnings of female immigrants found to be 14 percent less than those of comparable native female employees. This double disadvantage is concentrated among female immigrants with third level degrees.
Keywords: 330; Einkommen; Migranten; Schätzung; Irland